Socialization and Demonstration Utilization of Citraimona Plants (Cymbopogon nardus L. Rendle) as an Anti-Mosquito Spray Product in Taba Air Pauh Village - Banon, Charles; Putranto, Agus Martono Hadi; Sari, Amalia Upida; Novianti, Feni Mia; Zahra, Asty Alifah; Yana, Risti; Qotimah, Wahyu Ningsi (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2023)
Mosquitoes are often considered to disrupt human life. Various efforts are used to reduce the mosquito population, including using anti-mosquito spray. The anti-mosquito spray that is usually used is chemical-based. This is due to the public's lack of knowledge about the use of plants around them, such as citronella, to be used as an anti-mosquito spray. Therefore, activities were carried out aimed at increasing public understanding about the use of anti-mosquito spray, with a focus on plants around them, such as citronella which can be processed into useful ingredients. Through this outreach, we can provide useful information to the public, making them aware that citronella not only functions as a kitchen spice, but also as an ingredient in making an easy-to-make anti-mosquito spray. This research uses descriptive methods because it involves very specific experiments and research. This work program focuses on outreach and training to the community, from teenagers to adults, regarding the use of anti-mosquito spray from citronella. This activity consists of a preparation stage and an implementation stage. Based on the results of community service in Taba Air Pauh village showed high enthusiasm from the community and had a positive impact on increasing knowledge about the dangers of mosquitoes, chemicals, and making mosquito repellent liquid.